Young adult perspectives on their respiratory health symptoms since vaping. Issue 4 (2nd October 2021) - Kechter, Afton; Schiff, Sara J.; Simpson, Kelsey A.; Ceasar, Rachel C.; Braymiller, Jessica L.; McConnell, Rob; Leventhal, Adam M.; Barrington-Trimis, Jessica L.
Abstract: Background: Vaping among young adults (YA) has been associated with adverse respiratory health outcomes. However, key gaps remain in the literature including perspectives from YA vapers on perceived respiratory health symptoms since vaping, how they describe those symptoms and related experiences, and factors to which they attribute their respiratory health symptoms. Methods : Participants ( N  = 35) were 18–25 years old and self-reported as currently vaping at least once per week. In-depth, semi-structured qualitative interviews were conducted using an open-ended interview guide designed to elicit respondents' subjective vaping-related experiences. We used a thematic analysis to interpret the transcripts. Results : Participants reported adverse respiratory health symptoms (e.g., phlegm, cough, pain in lungs) that some attributed to vaping. Participants compared what is known about vaping to what is known about combustible cigarettes and described continued use of vaping products despite perceived adverse respiratory health consequences. Some participants attributed their symptoms to preexisting medical conditions (e.g., asthma) and to heavy vaping. Some described a decline in exercise-related endurance since vaping. Some participants also reported that they experienced worse respiratory symptoms when using specific brands and products (e.g., JUUL and nicotine salt formulation). Conclusions : This study provides powerful accounts from YA vapers about their experience of respiratory health symptoms that they ascribe to vaping. Future research is needed to evaluate the prevalence and severity, as well as the risk and protective factors, of adverse respiratory health symptoms associated with vaping. Addiction prevention and treatment efforts for YA vapers may help curtail adverse respiratory health impact from vaping.